2014
DOI: 10.1089/jwh.2013.4468
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Infertility Among Male and Female Veterans Serving During Operation Enduring Freedom/Operation Iraqi Freedom

Abstract: Women Veterans are more likely than their male counterparts to seek care for infertility, and given their increasing numbers, the demand for infertility evaluation and care within Veterans' Affairs may increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…In 1 recent study characterizing self-reported lifetime infertility among OEF/OIF/OND women Veterans, 15.8% reported infertility. 13 However, given that previous studies focused on self-reported infertility and the present work focused only on clinical diagnoses and receipt of VA-paid infertility care, it is impossible to make direct comparisons.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In 1 recent study characterizing self-reported lifetime infertility among OEF/OIF/OND women Veterans, 15.8% reported infertility. 13 However, given that previous studies focused on self-reported infertility and the present work focused only on clinical diagnoses and receipt of VA-paid infertility care, it is impossible to make direct comparisons.…”
Section: Discussionmentioning
confidence: 93%
“…10 Exposure to sexual assault, including military sexual trauma (MST), has been historically linked with self-reported infertility among women Veterans, perhaps explaining some of the association between mental health conditions (ie, posttraumatic stress disorder and depression diagnoses are common among women Veteran with MST). 11,12 Most recently, Katon et al 13 utilized national survey data to examine self-reported infertility among male and female OEF/OIF/OND Veterans, including VA users and nonusers, and found 15.8% of women and 13.8% of men reported a lifetime history of infertility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After adjusting for confounding variables, they found similar rates of infertility between men and women; however, they noted that women veterans were more likely to seek care for infertility treatment. 58 Additional studies have demonstrated associations between elevated rates of lifetime sexual assault and infertility or lack of infertility evaluations in female veterans. 59 Given the varied definitions used for surveying the population for prevalence of infertility, direct comparisons between the military and nonmilitary populations are difficult.…”
Section: Risk For Infertilitymentioning
confidence: 99%
“…Almost 16% of Iraq and Afghanistan veterans self-report a lifetime history of infertility. 29 Data linking infertility or other reproductive health outcomes to certain exposures in the military are lacking. 2 However, women veterans may have questions regarding occupational exposures and fertility.…”
Section: Infertilitymentioning
confidence: 99%